Faktor Penyebab Rendahnya Kedisiplinan Siswa dalam Mengikuti Kegiatan Madrasah - Azis, Abd; R, Nur Fadhilatur; Zahro, Siti Nurfatimatul; Ersabela, Putri (AL-BURHAN, 2024)
This research aims to identify and analyze the factors that cause the low level of student discipline at Madrasah Aliyah Bustanul Ulum Pagerharjo Wedarijaksa Pati. Discipline is an important aspect of education, but students often face difficulties in maintaining adequate levels of discipline. The research method used is qualitative. The data collection technique uses questionnaires, interviews, and documentation. Meanwhile, the data analysis technique involves data reduction, data display, and data verification. The results of this research reveal that the factors that cause the low level of student discipline at Madrasah Aliah Bustanul Ulum Pagerharjo Wedarijaksa Pati are broadly divided into three, namely factors related to students' personalities, factors related to educators' attitudes, and environmental factors. This research has important implications for improving student discipline in madrasah. By understanding the factors that influence discipline, schools, and educators can develop more effective strategies to improve student discipline.Keywords: Causal factors, discipline, MA Bustanul Ulum